2002
DOI: 10.1253/circj.66.267
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Lipoprotein(a) and Endothelial Dysfunction in Normocholesterolemic and Non-Diabetic Patients With Angiographically Normal Coronary Arteries.

Abstract: ndothelial dysfunction, which can be proved by demonstrating loss of acetylcholine-induced vasodilation, is an early event of atherosclerosis in human coronary arteries 1,2 and seems to accelerate the progression of the atherosclerotic process. 3 In clinical studies, selective loss of endothelium-dependent vasodilation in response to acetylcholine (ACh) has been observed in not only angiographically atherosclerotic coronary arteries, but also in normal coronary arteries of hypercholesterolemic patients. 4,5 Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(27 reference statements)
2
9
0
Order By: Relevance
“…[5][6][7] In the present study, serum Lp(a) concentrations were significantly higher in the lower dose EM group than in the full-dose EM group, which suggests that Lp(a) affects the basal tone in patients with CSA.…”
Section: Lp(a) and Nitric Oxidesupporting
confidence: 41%
“…[5][6][7] In the present study, serum Lp(a) concentrations were significantly higher in the lower dose EM group than in the full-dose EM group, which suggests that Lp(a) affects the basal tone in patients with CSA.…”
Section: Lp(a) and Nitric Oxidesupporting
confidence: 41%
“…A possible reason for the absence of a relationship between the effect of thrombolytic therapy and serum Lp (a) levels in these reports, is that diabetes mellitus and hypercholesterolemia, which are more potent risk factors, may have masked the influence of Lp (a). Ioka, et al 21) examined the relation between serum Lp (a) levels and the endothelium-dependent vasoresponse to acetylcholine. They excluded patients with hypercholesterolemia and diabetes mellitus, and concluded that high Lp (a) levels might be a strong predictor of endothelial dysfunction in normocholesterolemic and non-DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects, coronary infusion of acetylcholine produces coronary vasodilatation where as in patients with CAD, it reduces large coronary artery diameter and de-creases coronary flow velocity , [20]. This variation in response is attributed to altered endothelial reactivity on patients with CAD [21]. Atropine, an anticholinergic agent when administered to patients with CAD, is expected to increase the ischemic threshold during TMST.…”
Section: Discussionmentioning
confidence: 99%